THE VALIDITY AND RELIABILITY OF INSTRUMENTS FOR MEASURING ELEMENTARY SCHOOL STUDENTS' EARLY MATHEMATICAL ABILITY - Aan Yuliyanto; Turmudi Turmudi; Ernawulan Syaodih; Dadan Rusdiana Saputra; Arie Dharmawan; Cahya Karisma Pertiwi (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Teachers need to understand students' early mathematical abilities before continuing learning on the next topic to retain the knowledge. This study aims to produce appropriate and reliable instruments for quality research related to early mathematical abilities. This research implemented R&D. The subjects were 113 sixth-grade students of the elementary school in Karawang. The instrument used was a test to measure early mathematical ability. Validity and reliability tests indicated that the five initial mathematical ability test items were considered valid, with r count > r table and p-value <0.05. The Cronbach's Alpha value was 0.875 (above 0.8 or high reliability). Thus, the five items of the early mathematical ability instrument on the volume of cubes and rectangular prisms can be used for further research to measure the same variables accurately. The results are not significantly different for the same subject even though the time and place are different.